Uji Porositas dan Kuat Tekan Batako Ringan Berbahan Dasar Limbah Pengolahan Emas (LPE) dengan Filler Pohon Pisang (FPP) - Sumbawaty, Nola; Ahzan, Sukainil; Prasetya, Dwi Sabda Budi (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2018)
[Title:  Porosity Test and Compressive Strength of Lightweight Brick Based on Gold Processing Waste (LPE) with Banana Tree Filler (FPP)]. Lightweight concrete bricks are made from gold processing waste (LPE) and banana tree filler (FPP) with cement, foam, and clear water. The purpose of making light brick to know the value of porosity and value of compressive strength. Lightweight brick is made with gold processing waste (LPE) and banana tree filler (FPP) consecutively is 250 ml of LPE + 1 layer of FPP, 250 ml of LPE + 2 layers of FPP, 250 ml of LPE + 3 layers of FPP, 250 ml of LPE + 4 layers of FPP . Hardening time is carried out for 22 days in sunlight unspoiled. Tests performed include: density test, porosity test, and compressive strength test. From the test results showed that the porosity value and compressive strength of lightweight concrete bricks with gold processing waste plus the filler of banana trees with the amount of cement in the fixed condition and drying time for 22 consecutive days, the density value 1349, 09 kg / m3, 1290 kg / m3, 1121.6 kg / m3, 1168.3 kg / m3, 1254 kg / m3 and compressive strength value of 2.43 MPa, 1.25 MPa, 1.68 MPa, 2.13 MPa, 1.32 MPa. The high value of porosity and compressive strength value is influenced by the amount of mixture of foam, banana tree filler (FPP) and stirring method